Arsenic speciation analysis in cow's milk and plant-based imitation milks by HPLC-ICP-MS - Permigiani, Isis Sabrina (2023)
Imitation milks based on vegetables have become relevant in recent years as a substitute for cow´s milk. Total and inorganic content of arsenic (As) determination in food is of utmost importance due to toxicological concerns. This study aimed to (1) optimize and validate a methodology for speciation analysis using anion exchange high performance liquid chromatography coupled to plasma mass spectrometry and (2) analyze the arsenic content in milk and imitation milks.Determination of As (III) and As (V) was done following a simple and innovative treatment, which consisted on the dilution of a small volume of sample in mobile phase and further filtration. Furthermore, acid microdigestion for total As determination with small amounts of acid and sample was optimized. The detection limits of the method ranged from 0.2 to 0.7 µg L-1. Regarding to arsenic content we found that imitation milks based on peanuts and nuts presented the lowest inorganic As content (between 1.7 to 1 µg L-1) whereas the highest values were found in imitations based on soy, rice and vetch (27.3, 13 and 8 µg L-1, respectively). The cow’s milk presented intermediate levels of inorganic As (4 µg L-1). Also, almond- and quinoa-based imitation milks showed inorganic As values below detection limits, so these imitation milks may be the safest to consume with respect to arsenic content